2020
DOI: 10.3390/met10081022
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Process Factors on Creating Defects, Mainly Lustrous Carbon, during the Production of Ductile Iron Using the Lost-Foam Casting (LFC) Method

Abstract: The purpose of this paper was to analyze the process factors affecting the occurrence of lustrous carbon defects in ductile cast iron castings when using the lost-foam casting (LFC) method. This phenomenon results in creating raw surface defects, which sometimes may even lead to cast iron scrapping. A series of trial melting batches were carried out for variable process assumptions. The analysis was performed to reflect, to the greatest extent possible, real foundry production conditions. Industrial tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As is generally known, the high proportion of fine particles must be compensated by an increased dosage of binder (as the size of the individual particles decreases, the total surface area of the sand increases significantly, thus increasing the consumption of binder to achieve the required strengths). However, this could have a negative effect on the gas regime of the mold (core)-metal system and the tendency to gas defects formation [15]. On the other hand, a required surface quality of the casting is generally ensured and the potential for metal penetration types of casting defects was significantly eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…As is generally known, the high proportion of fine particles must be compensated by an increased dosage of binder (as the size of the individual particles decreases, the total surface area of the sand increases significantly, thus increasing the consumption of binder to achieve the required strengths). However, this could have a negative effect on the gas regime of the mold (core)-metal system and the tendency to gas defects formation [15]. On the other hand, a required surface quality of the casting is generally ensured and the potential for metal penetration types of casting defects was significantly eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the filling speed is fast at first and then slow throughout the filling process, and the liquid metal takes a total of 2.2 s to fill the cavity. Another interesting phenomenon is that the liquid metal fills the cavity in a concave shape, which is called the wall attachment effect, which is commonly seen in the filling process of the LFC under high vacuum [39,45] . However, the introduction of the A356 inlay produces some different phenomena.…”
Section: (A5)-(a7)mentioning
confidence: 99%